Equity research report: BMW Group AG - Pereira, Francisco (2022)
This Equity Research report examines BMW Group’s position as one of the leading premium automakers with the main goal of assessing whether investors should buy, hold, or sell BMW’s shares. Upon analyzing the potential impacts from future trends and current business risks on BMW’s core operations, our valuation yields a price target of €91.35for 2022, resulting in a return of 5.32% and thus, a HOLD recommendation.